2012
DOI: 10.1016/j.psychres.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Psychopaths lack the automatic avoidance of social threat: Relation to instrumental aggression

Abstract: Psychopathy (PP) is associated with marked abnormalities in social emotional behaviour, such as high instrumental aggression (IA). A crucial but largely ignored question is whether automatic social approach-avoidance tendencies may underlie this condition. We tested whether offenders with PP show lack of automatic avoidance tendencies, usually activated when (healthy) individuals are confronted with social threat stimuli (angry faces). We applied a computerized approach-avoidance task (AAT), where participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
103
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 43 publications
14
103
3
1
Order By: Relevance
“…Instead, there was large individual variability, possibly reflecting individual differences in the degree to which angry vs. happy faces elicit defensive behavior; for example in aggressive vs. anxious individuals (Roelofs et al, 2009b, 2010b; Von Borries et al, 2012; see also for a review on the relation between anger and approach motivation, Carver and Harmon-Jones, 2009). Here, we exploit this individual variability in bodily freezing and demonstrate that it predicts the effects of emotional stimuli on instrumental action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, there was large individual variability, possibly reflecting individual differences in the degree to which angry vs. happy faces elicit defensive behavior; for example in aggressive vs. anxious individuals (Roelofs et al, 2009b, 2010b; Von Borries et al, 2012; see also for a review on the relation between anger and approach motivation, Carver and Harmon-Jones, 2009). Here, we exploit this individual variability in bodily freezing and demonstrate that it predicts the effects of emotional stimuli on instrumental action.…”
Section: Discussionmentioning
confidence: 99%
“…We have used happy and angry faces, because these emotional faces have been suggested to activate the appetitive (approach) and aversive (avoidance) motivational systems respectively (Roelofs et al, 2009a,b, 2010b; Volman et al, 2011; Von Borries et al, 2012). In contrast with emotional faces such as fear, disgust, sadness, for which the elicited behavioral tendencies may be complex (Marsh et al, 2005; Seidel et al, 2010), happy and angry faces have been shown to induce approach and avoidance behavioral tendencies respectively (Marsh et al, 2005; Roelofs et al, 2009a,b, 2010b; Seidel et al, 2010; Volman et al, 2011; Von Borries et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on motoric approach/avoidance to social stimuli using a computer joystick task showed that high psychopathy scorers display less avoidance of social threats (angry faces; Von Borries et al, 2012), but it is unknown whether this would extend to actual interpersonal distance regulation during social interactions. To investigate this question, we used a paradigm based on that developed by Kennedy et al (2009) to assess interpersonal distance preferences in a community sample varying in psychopathy.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were interpreted as signifying that angry expressions are perceived as aversive, whereas fearful expressions are perceived as appetitive. Many experiments have now examined the appetitive and aversive qualities of expressive faces, and have generally found, for example, happiness to be predominantly appetitive and anger to be predominantly aversive (Rotteveel & Phaf, 2004; Seidel, Habel, Kirschner, Gur, & Derntl, 2010; Theodoridou, Penton-Voak, & Rowe, 2013; van Peer et al, 2007; Vrijsen, van Oostrom, Speckens, Becker, & Rinck, 2013), although the degree to which these effects occur may be moderated by personality variables (Heuer, Rinck, & Becker, 2007; von Borries et al, 2012; Roelofs et al, 2010) or affiliation goals (Krieglmeyer & Deutsch, 2013). However, no study has replicated or adequately explained the original, seemingly paradoxical finding that fearful facial expressions elicit behavioral approach in perceivers.…”
mentioning
confidence: 99%